“You Don’t Just Get Over What Has Happened to You”: Story Sharing, Reconciliation, and Grandma’s Journey in the Child Welfare System - Varley, Autumn (First Peoples Child & Family Review, 2016)
This article ‘You Don’t Just Get Over What Has Happened to You’: Story Sharing, Reconciliation, and Grandma’s Journey in the Child Welfare System highlights the memories of the strong Anishinaabekwe, or Indigenous women, in my family circle, most notably my grandmother, mother, aunt, and sister. My maternal grandmother, Marie Brunelle, lived through the child welfare system in the late 1940s and became part of what is known today as the “Sixties Scoop.” This article emphasizes the legacies and the intergenerational impacts of the child welfare system in our family through storytelling. By examining our stories of resilience, healing, and reconciliation, we can understand our family’s history, our displacement from Anishinabeg traditional territory, and the strength and resilience of the women in my family.